Low-Frequency Carbon Recombination Lines - Konovalenko, A.A.; Stepkin, S.V.; Shalunov, D.V. (Радиофизика и радиоастрономия, 2001)
The low-frequency carbon recombination lines (with wavelengths up to twenty five and even more meters) became important means of the low-density interstellar plasma diagnostics. An impressive amount of astrophysical information was obtained over the past twenty years the carbon lines were detected in the frequency range from 12 to 1400 MHz. Correspondingly, the maximum principal quantum numbers of the observed interstellar atoms are more than 800. The medium in the direction of Cassiopeia A is the best studied object, which forms such features. The volume of data for other galactic sources is also increasing. The observation of lines from such highly excited atoms is a unique and effective method for probing the physical conditions of the low-density interstellar plasma as well as the important means for the study of the physics of the high Ridberg state atoms.